Gastric Electrical Stimulation as a New Treatment Modality for Refractory Nausea and Vomiting with Normal Gastric Emptying - Jeff Angelo Taclob MD; Brian J. Lee DO; Andrew J. Ortega DO; Irene Sarosiek MD; Richard W. McCallum MD (SAGE Publishing, 2023)
Nausea and vomiting are cardinal symptoms affecting many patients with delayed or normal gastric emptying. The current therapies are very limited and less than optimal. Therefore, gastrointestinal symptoms persist despite using all the standard approaches for gastroparesis, functional dyspepsia, or unexplained nausea and vomiting. It is well established that gastric electrical stimulation (GES) is effective in reducing nausea and vomiting in gastroparesis, but there are essentially no data available that detail the efficacy of GES in symptomatic patients without gastroparesis. We present a unique case of a female patient diagnosed with functional dyspepsia, whose nausea and vomiting which were refractory to all standard therapies were successfully addressed with the implantation of a GES system.